Differentiating Dissociative from Non-Dissociative Disorders: A Meta-Analysis of the Structured Clinical Interview for DSM Dissociative Disorders (SCID-D): Journal of Trauma and Dissociation. Issue 1 (1st January 2021) - Mychailyszyn, Matthew P.; Brand, Bethany L.; Webermann, Aliya R.; Şar, Vedat; Draijer, Nel
ABSTRACT: Inaccurate diagnosis of dissociative disorders (DDs) remains a frequent problem. Misdiagnoses may lead to delayed or ineffective treatment, and subsequently poorer quality of life for those struggling with DDs, who frequently utilize mental health treatment and evidence high rates of self-harm and suicidality. This study's objective was to examine the magnitude of the effects with which the Structured Clinical Interview for DSM-IV Dissociative Disorders (SCID-D) and revised version (SCID-D-R) – henceforth referred to as the "SCID-D interviews" – provide diagnoses of DDs and differentiate them from nondissociative disorders as well as factitious and simulated dissociative presentations. For inclusion, studies had to be empirical investigations comparing SCID-D data of DD populations with other populations. Using combined methods of searching for "SCID-D" in electronic indexing databases, seeking recommendations from experts, and reviewing reference sections of identified studies, 15 studies were identified and subjected to meta-analytic review. Analyses showed that the overall SCID-D interview score (effect size 3.12) as well as each of the five subscales – particularly amnesia and identity alteration (effect sizes 2.16 and 2.87, respectively) – significantly differentiated DD from non-DD. Findings suggest that the SCID-D interviews show good validity identifying and differentiating those with DDs as compared to those without DDs. The SCID-D interviews are valid instruments for diagnosing and differentiating DD from other psychiatric disorders and feigned presentations of DD. Clinicians, researchers, and forensic experts can use the SCID-D interviews with confidence to make differential diagnoses of DDs. Future research using the SCID-D interviews is discussed.